BALANCED SCORECARD: MANAGEMENT TOOL FOR COMMERCIAL AND TOURISM ADMINISTRATION - Zambrano, Gema Viviana Carvajal; Quintero, Frank Ángel Lemoine; Rivera, Dianelys Nogueira; Alfonso, Yanelis Ramos (Seven Editora, 2025)
This research addresses the importance of evaluating and improving the implementation of competitive strategies in organizations, using the Balanced Scorecard as a management tool. In a context of constant economic, social, technological and environmental changes, it seeks to identify deficiencies in strategic execution and propose solutions to strengthen adaptation and anticipation of change. The objective of the study is to analyze the gaps between the calculated indices and the expected levels in different organizational perspectives, in order to propose improvements that optimize overall performance. To meet the proposed objectives, a mixed approach was employed, combining quantitative and qualitative methods. The method of analysis and synthesis was used to define the theoretical references and characterize the problem, and the empirical-analytical method to obtain a direct perception of the object of study and verify the hypothesis raised. The tools included scientific observation to identify problems and characterize the tourist destination, and surveys and interviews to delve deeper into consumer behavior. The study population included experts in strategic management and consumers in the tourism sector. The most relevant scientific results of the study highlighted the effectiveness of the Balanced Scorecard in detecting and addressing gaps in strategy implementation, providing a framework for continuous evaluation and timely adjustment of strategies. This underscores the importance of having clear indicators and well-defined objectives to improve organizational management. DOI: https://doi.org/10.56238/sevened2024.037-183